Wearable devices and healthcare: Data sharing and privacy. Issue 1 (1st January 2018) - Banerjee, Syagnik (Sy); Hemphill, Thomas; Longstreet, Phil
ABSTRACT: Wearable devices introduce many new capabilities to the delivery of healthcare. But wearables also pose grave privacy risks. Furthermore, information overload gets in the way of informed consent by the patient. To better protect American patients in an increasingly digital world, the U.S. Congress passed the Health Insurance Portability and Accountability Act of 1996 (HIPAA). This article examines the adequacy of HIPAA vis-à-vis issues raised by wearable technologies in the Internet of Things environment and identifies policy gaps and factors that drive health data exposure. It presents a 2 × 2 Partnership-Identity Exposure Matrix, illustrates implications in four different contexts, and provides recommendations for improving privacy protection.